Multi-dimensional optical data writing techniques for cloud-scale archival storage - Anderson, Patrick; Aranas, Erika B.; Black, Richard; Bucciarelli, Stefano; Caballero, Marco; Cameron, Pashmina; Canakci, Burcu; Chatzieleftheriou, Andromachi; Clegg, James; Cletheroe, Daniel; Cooper, Bridgette; Deegan, Tim; et al. (SPIE Photonics West, 2023)
The demand for long-term data storage in the cloud grows continuously into the zettabytes. Operating at such scales requires a fundamental re-thinking of how we build large-scale storage systems to archive data in a sustainable and cost effective manner. In Project Silica, a storage technology for the cloud is being designed and developed from the media up by leveraging the recent progress in ultrafast laser nano-structuring of the transparent media. Together with the advances in reading, decoding and error correction processes, high-density and high-throughput multi-dimensional volumetric optical data writing is achieved, enabling successful end-to-end proof-of-concept demonstrations of the technology. With exceptional media longevity, this could transform archival cloud storage. Here we briefly discuss the development of the technology, key metrics for cost-efficient optical data storage at scale, and successful proof-of-concept demonstrations.